The past, present, and future of 1.26T2. (26th April 2019) - Rovnyak, David
Abstract: This mini‐review considers the scientific and historical development of the constant 1.26 T 2, which represents the acquisition time for which the signal‐to‐noise ratio of a decaying exponential (with time constant T 2 ) is a maximum in the presence of thermal noise. While first reported in 1977, interest in this result greatly increased after about the year 2000, when it began to influence thinking in nonuniform sampling, sensitivity, and pulse sequence design. Overall, 1.26 T 2 has become a lens through which to view the evolution of NMR data acquisition and processing. An enduring lesson of the 1.26 T 2 story is the value of describing and analyzing the properties of magnetic resonance signals in the time domain prior to any further spectral analysis and processing, a concept which is at the core of many modern analytic techniques.